Predicting the potential distribution of three medicinal Gentiana species in China under climate change scenarios with the MaxEnt model - Luo, Jun; Li, Xinyu; Liu, Ying; Zhang, Shiyu; Liu, Anli; Liu, Ying; Zhou, Ying (Frontiers in Plant Science, 2026)
The genus Gentiana is concentrated in the Qinghai-Tibet Plateau and adjacent Hengduan Mountains, with its distribution pattern reflecting the synergistic effects of geological and climatic changes. This study employs the MaxEnt model integrated with ArcGIS spatial analysis to predict the potential geographical distribution of three medicinal Gentiana species (G. rhodantha, G. cephalantha, and G. rigescens) in China under current and future climate scenarios (SSP126 and SSP585). Under future climate warming, our projections indicate an overall reduction in suitable habitat area for all three species, with G. rigescens experiencing the most severe habitat loss. Furthermore, the centroid of suitable habitats is projected to shift towards higher latitudes and elevations, reflecting a spatial adaptation strategy to climate change. The key environmental drivers of distribution were identified: annual precipitation (Bio12) and minimum temperature of the coldest month (Bio6) primarily determine the distribution of G. rhodantha, while temperature seasonality (Bio4) and altitude are the dominant factors for G. cephalantha and G. rigescens. Our projections indicate an overall reduction in suitable habitat area for all three species under climate warming, with G. rigescens experiencing the most severe loss. Furthermore, the centroid of suitable habitats is projected to shift northwestward and upward in elevation. These findings highlight species-specific responses to climatic factors and provide a scientific basis for prioritizing the conservation of current highly suitable areas (e.g., Yunnan, Sichuan, and Guizhou), establishing ecological corridors, and implementing ex-situ conservation and sustainable cultivation practices to mitigate the impacts of climate change on these valuable medicinal resources.